Maternal sepsis update: current management and controversies - Greer,O; Shah,NM; Johnson,MR (The Obstetrician & Gynaecologist, 2020)
•Sepsis is a leading cause of maternal morbidity and mortality, globally and in the UK.•In pregnancy and the puerperium, women may be more susceptible to rapid deterioration of illness following an infection.•Sepsis has a complex pathophysiology and the immunological and cardiovascular adaptations of normal pregnancy may have an adverse impact on the maternal response to infection. Furthermore, physiological changes of pregnancy, which mimic those of sepsis, often delay optimal management.•‘Bedside’ identification of pathogens and their antibiotic resistance patterns may help to improve clinical outcomes.•Recent updates in sepsis management, areas of controversy and the importance of translational research and clinical trials for pregnancy and the puerperium are discussed.